EFEKTIFITAS MODEL PEMBELAJARAN GROUP INVESTIGATION BERBASIS LABORATORIUM TERBUKA TERHADAP KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR KOGNITIF SISWA - hanan, Abdul; Hunaepi, Hunaepi; Fitriyan, Herdiana i (Jurnal Ilmiah IKIP Mataram, 2019)
The purpose of this study was to determine the effectiveness of an open laboratory Group Invetigation learning model on science process skills and cognitive learning outcomes of students. This research is a quasi-experimental study. The study sample consisted of 36 students divided into experimental classes and control classes. Data collection techniques in the form of performance appraisal for science process skills and tests to assess students’ cognitive abilities. The results showed that the science process skills of the experimental class students average 80 with high categories. The results of the t test are obtained tcount (1.52) <t table (1.69). This shows that the laboratory-based Group Invetigation learning model is open to science process skills and ineffective student cognitive learning outcomes.Keywords: Group Investigation, Laboratory, KPS and Cognitive Learning Outcomes